A sátira política em O Pirralho: Juó Bananére e o Hermismo - 1911 a 1915 - Borges, Augusto Cesar Mauricio (2009)
This research studies the phenomenon of political satire in the city of São Paulo's Belle Époque, specifically the chronic character of the irreverent comedy Juó Bananére, pseudonym of Alexander R. M. Machado, on the then President of the Republic Marshal Hermes da Fonseca and bureaucracy that tied the body of political support. Our study indicated that part of the so-called small press played a significant role in the development and dissemination of the contents of humorous political critique in the First Republic. As part of this process, the political satire of Juó Bananére not only fulfilled its role of social entertainment, but also has a critical function of load positioning and policy intervention. Due the particular historical juncture, the main issue of our work talkect to materials published by the periodic watching the harmony of all these satires with the political-matters agenda of the seminary O Pirralho and the oligarchies of São Paulo in the São Paulo defeat in the elections of 1910. Looking at the political satire from the years 1911 to 1915, under the administration of Hermes da Fonseca, this work drag the relevant debating about history, city, politics and humor discussing the work of Alexander R. M. Machado at the seminary O Pirralho